2019
DOI: 10.1002/yea.3432
|View full text |Cite
|
Sign up to set email alerts
|

A CRISPR/Cas9 method to generate heterozygous alleles in Saccharomyces cerevisiae

Abstract: Saccharomyces cerevisiae is a genetically facile organism, yet multiple CRISPR/Cas9 techniques are widely used to edit its genome more efficiently and cost effectively than conventional methods. The absence of selective markers makes CRISPR/Cas9 editing particularly useful when making mutations within genes or regulatory sequences. Heterozygous mutations within genes frequently arise in the winners of evolution experiments. The genetic dissection of heterozygous alleles can be important to understanding gene s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…We are fully aware that the current state of the art for iPSC studies is to use gene-corrected isogenic controls; however, the presence of compound mutations, such as those used in this study (CP2A mutation), makes the generation of individual controls impracticable. At the same time, it has been stated that the high efficiency of genome cutting and repair makes the introduction of heterozygous alleles by the standard CRISPR/Cas9 technique near impossible (EauClaire and Webb, 2019;Liang et al, 2020aLiang et al, ,b, 2021.…”
Section: Discussionmentioning
confidence: 99%
“…We are fully aware that the current state of the art for iPSC studies is to use gene-corrected isogenic controls; however, the presence of compound mutations, such as those used in this study (CP2A mutation), makes the generation of individual controls impracticable. At the same time, it has been stated that the high efficiency of genome cutting and repair makes the introduction of heterozygous alleles by the standard CRISPR/Cas9 technique near impossible (EauClaire and Webb, 2019;Liang et al, 2020aLiang et al, ,b, 2021.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that gene- and site-specific biases were also observed for Target-AID-mediated point mutagenesis. However, compared to site-specific point mutagenesis by CRISPR/Cas9 practices [ 54 56 ], the Target-AID system avoids high cell toxicity and some tedious processes, such as design and usage of heterology block or stuffer to prevent repeated recognition and cutting by the gRNA/Cas9 complex, preparation of donor DNAs, etc. Therefore, Target-AID could provide a powerful and effective tool to generate site-specific point mutagenesis in S. cerevisiae .…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that gene-and site-speci c biases were also observed for Target-AID-mediated point mutagenesis. However, compared to sitespeci c point mutagenesis by CRISPR/Cas9 practices [54][55][56], the Target-AID system avoids high cell toxicity and some tedious processes, such as design and usage of heterology block or stuffer to prevent repeated recognition and cutting by the gRNA/Cas9 complex, preparation of donor DNAs, etc. Therefore, Target-AID could provide a powerful and effective tool to generate site-speci c point mutagenesis in S. cerevisiae.…”
Section: Resultsmentioning
confidence: 99%